Karnoprawna ochrona rynku kapitałowego w świetle kryminalizacji bezprawnego prowadzenia działalności w zakresie obrotu instrumentami finansowymi - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article concerns the criminalization of unlawful activity related to trading of financial instruments. The given problem is analyzed on the background of existing forms of protection of the capital market. The paper presents also a wide analysis of the object of criminal protection and also of punishable behaviors of the offender and illegal activity related to trading of financial instruments.
Keywords: prawo karne gospodarcze; kryminalizacja; działalność nielegalna; rynek kapitałowy; instrumenty finansowe